Life trajectories of Belarusian and Chinese urban youth on the example of residents of Minsk and Hong Kong - Yuanlong, Zhao (Journal of the Belarusian State University. Sociology, 2026)
The article analyses the calendar of key biographical events in the lives of hypothetical generations of young people aged 20 to 39 in Minsk and Hong Kong based on the data of the international sociological survey using the methodology of the Generations and Gender Programme. The age dynamics and prevalence of the following events were determined: separation from parents, start of work, entering into a relationship with a regular partner, start of cohabitation with a partner, marriage, birth of a child. A high level of similarity was revealed in the life trajectories of Belarusian and Chinese urban youth in such characteristics as early separation from parents and start of work. At the same time, significant differences were observed in terms of marriage and the birth of a child: these events were typical for the majority of representatives of Belarusian urban youth and, on average, occurred before the age of 30, whereas among Chinese urban youth they were much less common and, if they occurred, then closer to the age of 40.
Keywords: life course; life trajectory; urban youth; separation from parents; labour activity; matrimonial behaviour; reproductive behaviour